A construç\~ao de grandes barragens no Brasil, na China e na Índia: Similitudes e peculiaridades dos processos de licenciamento ambiental em países emergentes - Igor Ferraz da Fonseca (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This working paper examines the adoption of environmental licensing procedures in Brazil, India and China in the construction of dams and hydropower generation. Based on bibliographical and documental analysis, this paper shows some characteristics of environmental licensing processes of three dam projects internationally known for its great hydroelectric potential and also for its social and environmental impacts: the Belo Monte Dam, in Brazil; the Nu River hydroelectric complex, in China; and the Sardar Sarovar Dam, in India. The results shows that is possible to identify some similarities in the operation of environmental licensing procedures in these three countries. However, the national peculiarities make that these processes takes a unique character, marked by distinctions in the state configuration, patterns of interaction and conflict between government agencies and different ways of action assumed by organized civil society.
Keywords: Q48; Q58; 330; environmental licensing; hydropower dams; environmental policy; intragovernmental coordination; state capacities